Dissecting the role of the CRMP2–neurofibromin complex on pain behaviors. Issue 11 (November 2017) - Moutal, Aubin; Wang, Yue; Yang, Xiaofang; Ji, Yingshi; Luo, Shizhen; Dorame, Angie; Bellampalli, Shreya S.; Chew, Lindsey A.; Cai, Song; Dustrude, Erik T.; Keener, James E.; Marty, Michael T.; et al.
Abstract : Abstract: Neurofibromatosis type 1 (NF1), a genetic disorder linked to inactivating mutations or a homozygous deletion of the Nf1 gene, is characterized by tumorigenesis, cognitive dysfunction, seizures, migraine, and pain. Omic studies on human NF1 tissues identified an increase in the expression of collapsin response mediator protein 2 (CRMP2), a cytosolic protein reported to regulate the trafficking and activity of presynaptic N-type voltage-gated calcium (Cav2.2) channels. Because neurofibromin, the protein product of the Nf1 gene, binds to and inhibits CRMP2, the neurofibromin–CRMP2 signaling cascade will likely affect Ca 2+ channel activity and regulate nociceptive neurotransmission and in vivo responses to noxious stimulation. Here, we investigated the function of neurofibromin–CRMP2 interaction on Cav2.2. Mapping of >275 peptides between neurofibromin and CRMP2 identified a 15-amino acid CRMP2–derived peptide that, when fused to the tat transduction domain of HIV-1, inhibited Ca 2+ influx in dorsal root ganglion neurons. This peptide mimics the negative regulation of CRMP2 activity by neurofibromin. Neurons treated with tat-CRMP2/neurofibromin regulating peptide 1 (t-CNRP1) exhibited a decreased Cav2.2 membrane localization, and uncoupling of neurofibromin–CRMP2 and CRMP2–Cav2.2 interactions. Proteomic analysis of a nanodisc-solubilized membrane protein library identified syntaxin 1A as a novel CRMP2-binding protein whose interaction with CRMP2 was strengthened in neurofibromin-depleted cells and reduced by t-CNRP1. Stimulus-evoked release of calcitonin gene–related peptide from lumbar spinal cord slices was inhibited by t-CNRP1. Intrathecal administration of t-CNRP1 was antinociceptive in experimental models of inflammatory, postsurgical, and neuropathic pain. Our results demonstrate the utility of t-CNRP1 to inhibit CRMP2 protein–protein interactions for the potential treatment of pain. Abstract : Supplemental Digital Content is Available in the Text.t-CNRP1, a bifunctional calcium-channel allosteric inhibitory CRMP2 peptide, was antinociceptive in experimental models of inflammatory, postsurgical, and neuropathic pain.